Fabrication of a magnesium-ion-conducting magnesium phosphate electrolyte film using atomic layer deposition. (11th March 2020) - Tsuruoka, Tohru; Tsujita, Takuji; Su, Jin; Nishitani, Yu; Hamamura, Tomofumi; Inatomi, Yuu; Nakura, Kensuke; Terabe, Kazuya
Abstract: We successfully fabricated a magnesium phosphate film as a solid-state electrolyte (SSE) using plasma-assisted atomic layer deposition (ALD). By developing a ternary process consisting of alternative Mg–O and P–O sub-cycles, very uniform amorphous films were formed at relatively low deposition temperatures ranging from 125 °C to 300 °C. It was found that lower temperature deposition induces multi-bonding states in the phosphate matrix, which forms a mixture of pyrophosphates and metaphosphates. This results in increased hopping conduction of Mg ions in the disordered matrix. The film deposited at 125 °C exhibited higher ionic conductivities with a smaller activation energy than a sputtered magnesium phosphate film, which indicates the usefulness of ALD in fabricating Mg ion-conducting SSE films. The ALD film fabricated also showed reproducible conductivity and structural stability up to 400 °C.